PEMUKIMAN MILITER PENINGGALAN BELANDA DI BANDA ACEH (Kajian Komparasi Perkembangan Pemukiman Militer di Neusu Jaya dan Kuta Alam, 1900-2015) - Maisal Gusri Daulay; Husaini -; Teuku Abdullah (Universitas Syiah Kuala, 2017)
ABTRASCT This study raised the question of how the beginning of the establishment of military settlements in Neusu Jaya and Kuta Alam, how the transition function of the Dutch military buildings in Neusu Kuta Alam Jaya and from year to year and How Neusu state military settlements in Kuta Alam Jaya and at the present time. The purpose of this study was to describe all aspects related to the development of military settlements in Neusu Jaya and Kuta Alam. The data collection is done in three ways, namely interviews with informants. Informants in this study include members and clerks Iskandar Muda Military Command I, along with community Keuchik Gampong Neusu Jaya and Kuta Alam, Military Housing Residents, Retired Military and Staff Institute for Preservation of Cultural Property (BPCB). Documentation on the library archives and documents originating from the Military District Command I IM, and direct observation to the study site. The method used is critical historical method with qualitative approach. The results of data analysis showed that the beginning of the establishment of military settlements in Neusu Kuta Alam Jaya and is a relic of the Dutch Colonial. The Netherlands chose Neusu Jaya area and Kuta Alam as its military base because the area is very strategic and profitable for the Dutch colonial administration. Transition function of military buildings in Neusu Kuta Alam Jaya and appropriate authority of the government in power. During the Dutch colonial buildings are owned by the Dutch. At the time of the building occupied by the Japanese and the Japanese military occupied military post independence. At the current state of military settlements in Neusu Kuta Alam Jaya and can be said to be groomed and neat because it is directly under the control of the Military District Command I IM. In terms of preservation of cultural heritage sites the government has always tried to care for and preserve cultural heritage buildings in the military settlements, through cooperation programs and Army BPCB I IM. For the people that are around military settlements, the place is an attraction in itself in the city of Banda Aceh. ABSTRAK Penelitian ini mengangkat masalah tentang bagaimana awal mula berdirinya pemukiman militer di Neusu Jaya dan Kuta Alam, bagaimana peralihan fungsi bangunan militer Belanda di Neusu Jaya dan Kuta Alam dari tahun ke tahun dan Bagaimana keadaan pemukiman militer di Neusu Jaya dan Kuta Alam pada saat ini. Tujuan dari penelitian ini adalah untuk menjelaskan segala aspek yang berhubungan dengan perkembangan pemukiman militer di Neusu Jaya dan Kuta Alam. Pengumpulan data dilakukan dengan tiga cara, yakni wawancara dengan informan. Informan dalam penelitian ini meliputi anggota dan Pegawai Kodam I Iskandar Muda, Keuchik beserta masyarakat Gampong Neusu Jaya dan Kuta Alam, Penghuni Pemukiman Militer, Pensiunan TNI, dan Pegawai Balai Pelestarian Cagar Budaya (BPCB). Dokumentasi pada arsip perpustakaan dan dokumen-dokumen yang berasal dari Kodam I IM, dan observasi langsung ke lokasi penelitian tersebut. Metode yang digunakan adalah metode sejarah kritis dengan pendekatan kualitatif. Hasil analisis data menunjukan bahwa awal mula berdirinya pemukiman militer di Neusu Jaya dan Kuta Alam adalah peninggalan Kolonial Belanda. Belanda memilih daerah Neusu Jaya dan Kuta Alam sebagai basis militernya dikarenakan daerah tersebut sangat strategis dan menguntungkan bagi administrasi pemerintah kolonial Belanda. Peralihan fungsi bangunan militer di Neusu Jaya dan Kuta Alam sesuai otoritas pemerintah yang berkuasa. Pada masa kolonial Belanda bangunan tersebut milik Belanda. Pada masa Jepang bangunan tersebut ditempati Jepang dan pasca kemerdekaan ditempati militer TNI. Pada saat ini keadaan pemukiman militer di Neusu Jaya dan Kuta Alam bisa dikatakan terurus dan rapi karena berada langsung di bawah kendali Kodam I IM. Dalam hal pelestarian situs cagar budaya pemerintah selalu berusaha merawat dan melestarikan bangunan cagar budaya di pemukiman militer tersebut, melalui program kerjasama BPCB dan KodamI IM. Bagi masyarakat yang ada di sekitar pemukiman militer, tempat tersebut merupakan sebuah daya tarik sendiri yang ada di kota Banda Aceh.Kata kunci: Komparasi, Kuta Alam, Neusu Jaya, Pemukiman Militer.